The Use of Chitosan Coating to Maintain the Quality of Cherry Tomatoes (Lycopersicum esculentum var. cerasiforme) - Salsa Nurfadhillah; Rokhani Hasbullah (The University of Lampung, 2025)
Cherry tomatoes are prone to deteriorate during storage. Proper post-harvest technology is needed to maintain the quality of cherry tomatoes. This research aims to examine the effect of chitosan coating and storage temperature on the quality of cherry tomatoes and determine the optimal treatment. Cherry tomatoes of the Fortesta variety were used for experiment. Cherry tomatoes were dipped in chitosan solution with concentrations of 1% and 2%, and control. Each group of cherry tomatoes was then stored at temperatures of 15°C and 25°C. The research was arranged under a factorial completely randomized design with three replications. Measurement was performed on respiration rate, weight loss, firmness, total soluble solids, and organoleptic tests (freshness, color, and aroma) of cherry tomatoes. The results showed that chitosan coating affects the respiration rate, weight loss, firmness, total soluble solids, and organoleptic tests. Storage temperature affects respiration rate, weight loss, firmness, total soluble solids, and organoleptic tests. Chitosan coating of 2% concentration and storage temperature of 15°C were the best treatments that were able to suppress respiration rate, weight loss, firmness, total soluble solids, and were still accepted by panelists on the 21st day of storage. In contrast, the control only lasted until the 12th day of storage. Keywords: Cherry tomatoes, Chitosan, Cold storage, Edible coating, Quality.